IMPACT OF TOTAL QUALITY MANAGEMENT PRACTICES ON THE TRANSFORMATION TO ENTREPRENEURIAL UNIVERSITIES IN PALESTINE: THE MODERATING ROLE OF INNOVATION - Mohammad Kanan; Hala Dababat; Yahya Saleh; Ahmad Zaid; Ramiz Assaf; Siraj Zahran; Mahmoud Ali Salahat; Abdalmuttaleb Al-Sartawi (Operational Research in Engineering Sciences: Theory and Applications, 2023)
The increasing demand for a knowledge-based economy and the widespread influence of globalization have led to a significant transformation in higher education. This transformation has resulted in a departure from conventional paradigms and a shift towards the entrepreneurial university (EU) framework. The objective of this study is to examine the effects of adopting total quality management (TQM) principles on the process of transitioning traditional Palestinian universities into entrepreneurial universities (EUs). Furthermore, this research investigates the potential role of innovation as a moderating variable in facilitating the transformation process by means of adopting Total Quality Management (TQM) practices. In order to accomplish these aims, a thorough research model was established, utilizing a survey methodology for the purpose of data collecting. The research sample comprised senior management professionals from 18 Palestinian universities. A total of 44 questionnaires were collected from a subset of 12 selected institutions. The data analysis involved the utilization of the partial least squares structural equation modelling (PLS-SEM) method, which was implemented using Smart-PLS software. The findings indicate a noteworthy integration of Total Quality Management (TQM) strategies and innovation in Palestinian universities, accompanied by a moderate level of implementation in entrepreneurial activities. Moreover, the research findings suggest that the adoption of Total Quality Management (TQM) practises significantly and positively influences the shift towards Environmental Upgrades (EUs). Nevertheless, it is important to highlight that the presence of innovation does not exhibit a moderating influence on this particular association. This research contributes to the existing body of knowledge by demonstrating connections between three variables, offering empirical support for the integration of Total Quality Management (TQM) practises, innovation, and entrepreneurship in the Palestinian higher education setting. The results underscore the imperative for decision-makers inside Palestinian institutions to embrace effective Total Quality Management (TQM) practises, placing particular focus on information and analysis, as well as people management. The primary objective of this concentration is to foster entrepreneurial endeavours within the realm of higher education.